1946
DOI: 10.1001/archneurpsyc.1946.02300210003001
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Skin Resistance Test in Evaluation of Peripheral Nerve Injuries

Abstract: as a practical test in the evaluation of injuries of peripheral nerves. This method, in contrast to the sensory examination, does not depend on the cooperation of the patient. It can therefore be used with uncooperative, or even unconscious, patients and may give objective results in cases of hysteria or suspected malingering. Richter and Katz examined 10 patients with injury of the ulnar nerve and found a correlation of skin resistance with sensory changes in most of them. Of the 27 patients with various peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1947
1947
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The stimulation probably coactivated cutaneous vasoconstrictor fibres but since no significant changes of skin temperature occurred, it is unlikely that the vasoconstrictor activation affected the sweat responses. In agreement with previous anatomical data (Guttmann, 1940;Richter & Katz, 1943;Herz, Glaser, Moldover & Hoen, 1946) the correspondance between mechanoreceptor afferent sensory fields and sympathetically innervated fields was essentially good.…”
Section: Discussionsupporting
confidence: 91%
“…The stimulation probably coactivated cutaneous vasoconstrictor fibres but since no significant changes of skin temperature occurred, it is unlikely that the vasoconstrictor activation affected the sweat responses. In agreement with previous anatomical data (Guttmann, 1940;Richter & Katz, 1943;Herz, Glaser, Moldover & Hoen, 1946) the correspondance between mechanoreceptor afferent sensory fields and sympathetically innervated fields was essentially good.…”
Section: Discussionsupporting
confidence: 91%
“…The information obtained indicated that studies of peripheral autonomic function had a definite place in the objective, clinical evaluation of patients in whom the lesion was complete. In patients with incomplete peripheral nerve lesions, however, such studies were found to be of much more limited practical value, at least when attention was confined to the integrity of sudomotor fibres (Herz et al, 1946). The experience gained in the present work on vasomotor function might be taken to substantiate this belief.…”
Section: Discussionmentioning
confidence: 58%
“…Before the introduction of modern electrodiagnostic techniques for the study of nerve conduction velocity, a number of studies were undertaken on sudomotor and vasomotor function in patients with peripheral nerve injuries sustained usually while on military service (Doupe, 1943;Jasper and Robb, 1945;Herz et al, 1946). The information obtained indicated that studies of peripheral autonomic function had a definite place in the objective, clinical evaluation of patients in whom the lesion was complete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation